Effect of administrative management for the development of university competencies in Engineering students Campus Amazcala - Velázquez Hernández, Jorge Arturo; Alonso Chombo, Rosalía; Romero Zepeda, Jorge Adán (Advances in Social Sciences Research Journal, 2021)
Administration is a tool that helps to improve the internal issues of any institution as long as they are used correctly and effectively to address the areas of opportunity that may exist. The research aims to prove that proper management can help develop useful competencies for university students entering the world of work. The methodology implemented is quantitative in nature, using the survey technique. The universe studied was 72 students, considering a convenience sample due to the very small number of the population, since the main purpose is to corroborate or refute the proposed hypothesis where it is said that the Faculty of Engineering of the Amazcala Campus carries out its administration efficiently to verify that the teachers develop in the students the necessary labor competencies for their graduation to the professional field. Among the most important results, it was found that administrative management must communicate the agreements that are made and verify that students are acquiring the necessary knowledge for the professional field.